Urban poverty, growth, and inequality: A needed paradigm shift?. Issue 2 (21st February 2022) - Wilson, Edgar J.; Jayanthakumaran, Kankesu; Verma, Reetu
Abstract: This paper calculates poverty and inequality elasticities using the latest‐available World Bank primary survey household consumption expenditure data for the rapidly growing urban sectors of India, Indonesia, and China. Our approach compares the conventional use of the overly simple headcount measure to the poverty gap squared ( PG 2 ) measures of poverty and focuses the effectiveness of reducing inequality on the disutility of the poor using a microeconomic utility‐based point elasticity measure of poverty loss. The calculations show that reducing urban inequality is more effective in reducing (1) urban poverty than promoting growth and (2) poverty distress more than that in the rural sector. The optimal policy prescription is to reduce urban inequality by targeting the urban very poor using the PG 2 measure. Further research is required to identify and quantify the determinants of the point elasticity magnitudes and the possible directions of causation.